Utilização do Método dos Elementos Finitos na determinação de campos de tensões em corpos revestidos - Medeiros, Julliana de Paula (1996)
The use o f coatings has been a valuable practical procedure aiming the reduction o f the wearing o f mechanical components. Nevertheless, the high stress levels which generally appear when bodies are put into contact can lead to the failure o f the coated member. These mechanisms can be by microcracking, loss o f adherence and plastic deformation. This work addresses the determination o f stress distributions arising when a plane coated specimen is acted upon by a spherical penetrador, by using finite element analysis. The coating is supposed to be stiffer than the substrate. Furthermore, a perfect adherence between these two components is assumed. The finite element model is first validated by checking the obtained stress distributions against those provided by the classical Hertz theory. In the sequence, the influence o f the coating thickness upon the stress distributions and also upon the nature o f the failure mechanisms o f the composite specimen is examined. The effect o f friction on the contact interface is also considered. The numerical results show that, in general, the performance o f the composite specimen is very sensitive to the coating thickness, except for extremely thin coatings. It is found that the increase in the coating thickness leads to failure mechanisms which are likely to act inside the coating layer rather than in the interface coating-substrate. It is also found that friction is responsible fo r significant reduction o f tensile stresses on the specimen surface, fo r the whole range o f coating thickness examined.